Andamiar (2020)
The proposed project intends to provide a public space according to the reality of the Siete de Agosto neighborhood. The design proposes a typical module, which can be grouped in different ways, and which is adaptable to the social dynamics of the place. Furthermore, it is the artifact used to return nature to the sector by rethinking the flower pot, widely used in the neighborhood, on the scaffolding; as a new shelter for vegetation that is currently not present in the sector.